Impacts Of Service Quality, Satisfaction And Personal Factors On Student Retention In Open Distance Learning Institutions In Malaysia - Ng, Man San (2010)

(untitled)
The purpose of this study was to determine the impacts of service quality, student satisfaction and personal factors on student intention to complete study in open distance learning (ODL) institutions. A cross-sectional survey design was employed in this study. Data was collected during the period from October to December, 2009 from a nation-wide random sample of 450 Open University Malaysia (OUM) undergraduate students. Several statistical techniques were used to analyse the data and they include producing frequency counts for generating descriptive statistics. In addition, factor analysis was used to identify and confirm the factors of service quality, student satisfaction and student retention. Multivariate analysis was also used for testing hypotheses and measuring the impacts of factors on student retention. The study findings based on 342 usable questionnaires indicated that service quality and its four dimensions (tangibility, reliability, responsiveness, and assurance) had positive impacts on overall satisfaction. However, the empathy dimension did not have any effect. Five factors were found to have effects on student intention to complete study in OUM. They were: student satisfaction, goal commitment, family support, study habits and number of semesters attended. However, service quality had no effect. The findings indicated that low student retention in ODL institutions was attributed not only to student satisfaction but also to a combination of personal factors. It follows that the key to an effective retention strategy is for ODL institutions to provide quality support services that meet the satisfaction of the students. Additionally, ODL institutions should help the students to overcome their personal problems. (Abstract by author)